Reflections on practice: providing authentic experiences with families in early childhood teacher education. Issue 3 (3rd July 2021) - Winship, Morgan; Standish, Heather; Trawick-Smith, Jeffrey; Perry, Caroline
ABSTRACT: Teachers' positive relationships with families contribute to the social, emotional, and intellectual development of children in early childhood education programs. Effectively involving, communicating, and partnering with families requires a unique set of professional abilities. Teachers must hold a deep understanding of the cultural and socioeconomic needs and characteristics of families and possess social skills and dispositions that allow them to effectively engage the adults in children's lives in sensitive and supportive ways. Are preservice teachers of young children well prepared to carry out this important role in their teacher education programs? Although 60% of teacher education programs require a course on families, few include authentic experiences in which candidates interact with families face-to-face. In the present article, the four authors – a teacher educator, a supervising teachers, and two early childhood teacher education candidates – reflect on a project which included seven elaborate experiences with families in lieu of a traditional, required course. We share our diverse perspectives on the impact of each experience, presenting excerpts from candidates' reflective journal entries and from the field notes of the teacher educator and supervising teacher. Implications of our experiences for teacher education are presented.